Meanings of Interpersonal Relationships for Nursing in the Context of Hospital Care: Meanings of Interpersonal Relationships for Nursing in the Context of Hospital Care - Silveira Lima, Ana Laura; Gonçalves Barbosa, Tayna; Martins Silva, Yan Lucas; Veloso Dias, Orlene; Andrade Barbosa, Henrique; Andrade Sampaio, Cristina; Vieira, Maria Aparecida (Revista Unimontes Científica, 2023)
Objective: To understand the meanings of interpersonal relationships assigned by professionals and students in the nursing field in the dynamics of their work environment, using Symbolic Interactionism as a theoretical framework. Method: Exploratory study, with a qualitative approach, with 10 members of the Nursing area. The information was collected through semi-structured interviews and analyzed using the content analysis technique, with the use of the ATLAS.ti software. Results: The meanings related to the interpersonal relationship of the nursing team in the hospital context were identified, as well as facilitating and complicating aspects. Despite the emphasis given to weaknesses, the participants recognized factors favoring teamwork, such as a good interpersonal relationship, communication and recognition for the work done. Final Considerations: It is necessary to focus on communication in the nursing work process, emphasizing interpersonal relationships, their meanings and subjectivity, enabling the construction of common objectives among the team, in order to guarantee the promotion of complete care.